Estimating survival in the Apennine brown bear accounting for uncertainty in age classification - GERVASI, Vincenzo; BOITANI, Luigi; Paetkau, David; Posillico, Mario; Randi, Ettore; CIUCCI, Paolo (Population Ecology, 2017)
For most rare and elusive species, estimating age-specific survival is a challenging task, although it is an important requirement to understand the drivers of population dynamics, and to inform conservation actions. Apennine brown bears Ursus arctos marsicanus are a small, isolated population under a severe risk of extinction, for which the main demographic mechanisms underlying population dynamics are still unknown, and population trends have not been formally assessed. We present a 12-year analysis of their survival rates using non-invasive genetic sampling data collected through four different sampling techniques. By using multi-event capture–recapture models, we estimated survival probabilities for two broadly defined age classes (cubs and older individuals), even though the age of the majority of sampled bears was unknown. We also applied the Pradel model to provide a preliminary assessment of population trend during the study period. Survival was different between cubs [φ = 0.51, 95% CI (0.22, 0.79)], adult males [φ = 0.85, 95% CI (0.76, 0.91)] and adult females [φ = 0.92, 95% CI (0.87, 0.95)], no temporal variation in survival emerged, suggesting that bear survival remained substantially stable throughout the study period. The Pradel analysis of population trend yielded an estimate of λ = 1.009 [SE = 0.018; 95% CI (0.974, 1.046)]. Our results indicate that, despite the status of full legal protection, the basically stable demography of this relict population is compatible with the observed lack of range expansion, and that a relatively high cub mortality could be among the main factors depressing recruitment and hence population growth.